Inovasi Layanan JAMILA (Jaminan Layanan Prima Mengantar Buku Andalan Ke Pemustaka) pada Perpustakaan Kota Yogyakarta - Septiara, Dara; Aiman, Nur; Masruri, Anis (Librarium: Library and Information Science Journal, 2025)
This study aims to analyze the Jamila service innovation (Guarantee of Excellent Service Delivering Reliable Books to Users) implemented in the Yogyakarta City Library. Jamila service is a form of book delivery service based on "delivery service" designed to make it easier for users to access library materials without having to come directly to the library. This study uses a qualitative descriptive method with data collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The results of the study indicate that service innovation includes expanding user requirements, such as access for users domiciled outside Yogyakarta with a meeting location arrangement (COD), as well as updating procedures involving the use of technology such as OPAC and WhatsApp for service efficiency. The obstacles found include inaccuracy of delivery location points and weather obstacles, which affect service effectiveness. However, the library has overcome most of the previous obstacles, such as transportation and promotion, through the use of official vehicles and social media. This study concludes that Jamila service innovation has succeeded in increasing the accessibility of library services, providing convenience for users, and can be a model of service innovation for other libraries in Indonesia.